2021
DOI: 10.18632/aging.202778
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced miR-27 and miR-195 regulate ATP consumption, viability, and metabolism of rat cardiomyocytes by targeting PPARγ and FASN expression

Abstract: This study examined whether hypoxia-induced microRNA (miRNA) upregulation was related to the inhibition of chondriosome aliphatic acid oxidation in myocardial cells under anoxia. We showed that anoxia induced high expression of hypoxia-inducible factor-1-alpha, muscle carnitine palmitoyltransferase I, and vascular endothelial growth factor in cardiomyocytes. Meanwhile, miR-27 and miR-195 were also upregulated in hypoxia-induced cardiomyocytes. Furthermore, hypoxia induction led to reductions in the adenosine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…On the other hand, we do not clarify how baicalein up-regulates PPARγ expression. Several lines of evidence have identified PPARγ as a direct target of miR-27 [ 48 , 49 ]. Baicalein serves as a regulator of many miRNAs [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we do not clarify how baicalein up-regulates PPARγ expression. Several lines of evidence have identified PPARγ as a direct target of miR-27 [ 48 , 49 ]. Baicalein serves as a regulator of many miRNAs [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the ectopic expression of miR-195 suppresses the expression of INSR , thereby impairing the insulin signaling cascade and glycogen synthesis in HepG2 cells ( Yang et al, 2014 ). Meanwhile, miR-195 is able to target FNAS to regulate ATP consumption and cell migration ( Mao et al, 2012 ; Lin et al, 2021 ). This suggests that the same miRNA will serve different functions depending on the target genes.…”
Section: Discussionmentioning
confidence: 99%
“…169 Studies have suggested that miR-27 and miR-195 are also upregulated in hypoxia-induced cardiomyocytes, suppressing the expression of ACLY and ACC. 170,171 The mechanism of ACLY regulation in tumor cells under hypoxic conditions is still unclear. ACC (including ACC1 and ACC2) is the rate-limiting enzyme in the FA synthesis pathway.…”
Section: Lung Adenocarcinomamentioning
confidence: 99%